Highlands sustainable development and tourist’s satisfaction: a grounded model study / Ang Kean Hua - Ang, Kean Hua (Faculty of Health Sciences, Universiti Teknologi MARA, 2018)
This study investigated the factors affecting tourist’s satisfaction visiting highland tourism destination based on the grounded model study. The district officers, environmental officers, non-government organization, as well as local residents and farmers were approached via semi-structured interviews to gather information. Five core themes emerged from the qualitative data analysis, namely tourism development impact, sustainable development impact, environmental impact, educational factor, and tourist’s satisfaction. The model was further validated with quantitative survey study involving 420 Cameron Highlands, Malaysia tourists. Partial least squares structural equation modeling (PLS-SEM) analysis was conducted to validate the instruments and analyse the hypothesised relationship. This study confirmed that tourism development, environmental impact, and education factor are important factors affecting highland tourist’s satisfaction. This study developed the highland tourist’s satisfaction model, which can be used as a reference for investigating tourist’s preferences and satisfaction specifically in highland tourism destination.